Model Keteladanan Pengelolaan Pendidikan Islam K.H. Hasyim Asy’ari - Suhada, Suhada; Fauzi, Anis; Firdaos, Rijal (Udayana University Press bekerjasama dengan Fakultas Ilmu Budaya Universitas Udayana, 2024)
This article aims to explain the meaning of Islamic education and explain the intellectual impact of K.H. Hasyim Asy’ari on the implementation of Islamic education. The research methodology used in this research is library research, which includes reading, writing and analyzing research materials, as well as utilizing library-centered information collection strategies. The author uses content analysis as a method for analyzing data in this research. Content analysis is used to compare the findings of a study with other studies related to the same issue. Textbooks and journal articles serve as sources of knowledge used to prepare this article. The research problem revolves around two key questions: